Barriers experienced by and educational needs of clinicians who provide care for transgender, nonbinary, and gender-diverse young adults in the Mid-Atlantic and Southern United States. - Jessica Kremen; Meg Quint; Regina Tham; Kaiden Kane; Elizabeth R Boskey; Cassandra Morrow; Sari L Reisner; Rena Xu (PLoS ONE)
Purpose The purpose of this study is to identify and explore the educational needs of and broader barriers experienced by clinicians who provide care to transgender, nonbinary, and gender diverse (TGD) young adults (aged 18-24), with a focus on unique healthcare needs and challenges. Methods Between April 2022 - July 2022, we conducted qualitative interviews with 13 clinicians (n = 9 medical and n = 4 mental health) about perceived needs and barriers relating to the care of TGD young adults. Clinicians were recruited throughout the Southeastern and Mid-Atlantic United States and were a mix of general practitioners and specialists. Using a hybrid deductive and inductive thematic analysis approach, the interview transcripts were analyzed and key themes identified. Results Thematic analyses of these interviews identified three main themes: the need for knowledgeable clinicians, the need and desire for reliable training resources and mentorship, and concerns surrounding the impact of the sociopolitical environment. Many participants noted a lack of access to local educational opportunities and mentorship but expressed willingness to seek these out if centralized resources, such as national platforms or accessible training modules, were available. Conclusion This study identifies both gaps in clinician education and broader barriers - such as local politics and access to mentorship - that hinder the ability to provide effective care to TGD young adults. These findings will help to inform the development of clinician education and support programs.